Pemanfaatan Cloud Computing dalam Revolusi 4.0 - Asnawati Asnawati; Liza Yulianti; Feri Hari Utami; Eko Suryana; Irvan Ciantury (Universitas Dehasen Bengkulu, 2022)
Technology has changed the way people communicate, interact and act in various tasks and activities. One of them is how people store digital data in a storage medium. Conventional storage media such as hard drives, flash disks, CD/DVDs have begun to be abandoned. One of the reasons it has started to be abandoned is that important data is often lost along with the loss of the media. Technology, especially the internet, has become one of the solutions in the world of media storage, namely the presence of cloud technology through strong cloud. In addition to being the answer, the internet is also a means of communication through weblogs or often abbreviated as blogs. Weblogs can be an effective medium of information about an organization's activities. These two things are behind the plan for community service activities at SMKN 2 Bengkulu Tengah. For teachers, strong cloud technology has been introduced through lectures and direct training, while for students they have been trained how to design a weblog according to the needs of the school, especially the students. Teachers can take advantage of the many advantages of cloud storage for various purposes. Students of SMKN 2 Bengkulu Tengah can have a means of communication and a creative arena with webloging activities.